A Metallurgical Study of Micro Plasma Arc Welded Joint of Austenitic Stainless-steel Blank - V. Haldar; S. Pal (Archives of Metallurgy and Materials)
Micro plasma arc welding (MPAW) is frequently used for joining thin sheets of ferrous and nonferrous materials. In this study, austenitic stainless steel 316L of 0.5 mm thin sheets are joined by using MPAW. The weld metallurgy is characterized by field electron scanning microscopy (FESEM), Transmission electron microscopy (TEM), and X-ray diffraction (XRD) techniques to evaluate different phases formation and their orientation in detail. Mechanical tests like tensile test, micro hardness test is also carried out to measure the joint quality. It is found that the weld joint is constituent of two major phases, δ-ferrite and austenite (γ), and few secondary phases like chromium carbides. The ferrite percentage in the fusion zone is higher than the as received base material. The fusion zone hardness is increased due to the presence of high amount of ferrite and carbides. The tensile fracture surface contains lots of dimples and voids, which indicates good ductility of the joint. A defect free and good joint efficiency is achieved by using MPAW.